PARTISIPASI MASYARAKAT LOKAL DALAM PARIWISATA (STUDI KASUS DI DESA WISATA BELIMBING, TABANAN, BALI) - Ni Luh Gede Ratnaningsih; I Gusti Agung Oka Mahagangga (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2015)
ABSTRACT This research is motivatedbythe management ofthe Belimbing Tourism Village, thenew attraction. The natural beauty oftherice terracesare, waterfalls, plantationsandtemplesMekori. Notless interesting tothe cultureasa traditionalwayto make palm sugarandhow togrow rice. Belimbing declarationvillageas a tourist villageon25 November 2010has provideda positiveimpactto thedevelopment ofBelimbing Tourism Village. Responsesocietyin economic termsthatpeopletake advantage ofemployment and business opportunitiesthat existafterthe development ofthe Belimbing Tourism Village. Sucha way to openshop, villas, homestaysandbecomeemployees ofthe villaand tour guides. The method usedin this researchisdescriptivequalitativemethod. This studyis expected tobe usefulin providingadviceandsolutions toproblems facedin the developmentandmanagement of Belimbingtourism village. Another is theexpectationwith thedevelopment ofthe villageas a Belimbing Tourism Villageexpected to be abletoimprovethe economic, socialand cultural. Based on the resultsof localcommunityparticipationinthetourismactivitiesthatinclude: 1. Shapeparticipationof tourismactivitythat started theinitialdevelopmentin which public participationbeganin 1982.In that year, the community seesincreasing numbers of touristswhostopatrice terracesbelonging tothe community. 2. Shapeparticipation inthe communityisresponding tothe tourismbusiness opportunities, such asmakingrestaurant, villasandhomestayaccommodationas well aspeopleworkinginthere. 3. Shapeparticipation inthecommunityplanningthatmakesthe governing bodyand groupstravelmanagementBelimbing Tourism Village. 4. Shapes society participation in the implementation of the plan that had been developed previously. Like making structure governing body and Pokdarwis. 5. Shapeof participationinthatcommunity continues toimprovesustainabilityperformancetodevelop Belimbing tourism villageforsustainability. 6. Shapeparticipationin the evaluation ofprogramsthatthe community continues todo an evaluation ofallthe planningthathas beendone.